Analisis Tanggung Jawab Bank Terhadap Kebocoran Data Nasabah: Ditinjau Dalam Perspektif Hukum Perbankan - Wildan, Muhammad; Ramadhan, Daud Renata Candra; Wijayanti, Zulfa Rena (Media Hukum Indonesia (MHI), 2024)
Data breaches involving bank customers are a critical issue in modern banking, with significant impacts on both customers and the reputation of banks. This study analyzes the legal responsibilities of banks regarding data breaches in Indonesia, focusing on applicable regulations, such as Law No. 10 of 1998 on Banking and Law No. 27 of 2022 on Personal Data Protection (PDP Law). The research employs a normative juridical method to examine banks' obligations to maintain the confidentiality and security of customer data. The findings indicate that banks have a legal duty to protect customer data, including ensuring security systems capable of addressing threats like cyberattacks. Banks found negligent in fulfilling these duties may face administrative sanctions, criminal penalties, or damages. The study also identifies challenges in regulatory implementation, such as non-compliance by banks, weak oversight, and low awareness of data protection in the banking sector.